(untitled) (South East Asia Journal of Public Health, 2014)
The complex nature of adolescent sexual and reproductive health (ASRH) determinants demands a multidisciplinary and intersectoral approach. Collaborative approaches are central to the delivery of quality health care and services but the focus is often health sector specific. Few research studies have explored the views and experiences of health workers and teachers and examined how ASRH services and information are provided by professionals across the education and health sector. Sri Lanka has made considerable progress towards addressing the Millennium Development Goals (MDG), however, there are still gaps reflected in adolescent health, social indicators, and the delivery of services. Enhancing the collective efforts of teachers and health professionals may help to improve the quality and use of services and ASRH knowledge. This study aimed to identify the experiences, needs, knowledge, attitudes and practices of primary healthcare and education professionals and the strategies that best support them to deliver sexual and reproductive health information, education, counseling and clinical services to Sri Lankan adolescents. Qualitative and survey data were gathered from 65 nurses, midwives, public health inspectors, medical officers, teachers, counselors and principals in the district of Kalutara. Knowledge, attitudes and service gaps were identified in relation to contraception and policy guiding practice. Participants highlighted concerns with confidence, roles and training that were said to affect student access to appropriate health services. ASRH Collaborative practices were noted across the sectors and strategies suggested for improvement. Findings suggest that inter-professional educa-tion and training may provide opportunities to enhance collaboration supported and guided by appropriate policy, supervision and job descriptions (i.e. roles and responsibilities). South East Asia Journal of Public Health 2013; 3(1): 42-49 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17710